Causes of insecurity and its Management Strategies among Rural Dwellers of Bauchi Local Government Area of Bauchi State - Wan, Suleman Ahmed; Muhammad, Salisu Umar (Balai Publikasi Indonesia, 2025)
Insecurity is the phenomenon of being in a state where you are subject to danger or injury. It is the anxiety one experiences when he feels vulnerable and insecure. Therefore, this research study aims to investigate the causes of insecurity and the plight of rural dwellers in the Bauchi Local Government Area of ​​Bauchi State. However, the specific objectives of the study are to examine the nature and trends of insecurity, investigate causes of insecurity, find out the strategies that can be adopted to manage insecurity challenges, and understand the perceptions of people about insecurity in the Bauchi Local Government Area of ​​Bauchi State. We used a sample size of 100 respondents, consisting of adult males and females from four wards of the local government under study. The study adopted Durkheim's Theory of suicide. The study employed analytical tools such as frequency and percentage. We adopted both primary and secondary sources for data collection. In the field study and analysis, it was discovered that several illegal armed groups, ethnic militia groups, religious fundamentalists, and fanatics are evidence of insecurity in Nigeria. These groups have given rise to a series of incidents such as bombings, murders, arson, armed robberies, banditry, kidnapping, corruption, and injustice, all of which we hear about every day. These happenings are negatively affecting the Bauchi Local Government area in the Bauchi State of Nigeria politically, religiously, and culturally. Religious organizations and other humanitarian agencies are losing confidence in law enforcement agencies. This work, therefore, examines and shows the causes and effects of the political, religious, and cultural implications of insecurity in Nigeria. According to this research, there is a threat of political, economic, and civil destabilization if the trend of insecurity persists. This study recommends a stiffer penalty for perpetrators of violence and equipping law enforcement agencies with modern technological weapons, allowances, and proper recordkeeping.